Fuzzy-Based Adaptive Hybrid Burst Assembly Technique for Optical Burst Switched Networks - Muhammad Umaru, Abubakar; Abd Latiff, Muhammad Shafie; Coulibaly, Yahaya (Journal of Computer Networks and Communications, 2014)
The optical burst switching (OBS) paradigm is perceived as an intermediate switching technology for future all-optical networks. Burst assembly that is the first process in OBS is the focus of this paper. In this paper, an intelligent hybrid burst assembly algorithm that is based on fuzzy logic is proposed. The new algorithm is evaluated against the traditional hybrid burst assembly algorithm and the fuzzy adaptive threshold (FAT) burst assembly algorithm via simulation. Simulation results show that the proposed algorithm outperforms the hybrid and the FAT algorithms in terms of burst end-to-end delay, packet end-to-end delay, and packet loss ratio.